2019
DOI: 10.1002/csr.1754
|View full text |Cite
|
Sign up to set email alerts
|

Corporate images and customer behavioral intentions in an environmentally certified context: Promoting environmental sustainability in the hospitality industry

Abstract: Growing environmental awareness has made customers change their attitudes and increasingly demand that the hospitality industry provides products and services that are environmentally friendly. This sector faces increasing pressure to operate in a more ecofriendly manner given its negative influence on the natural environment.Extant research demonstrates that sustainable tourism can be promoted through environmental certifications. However, little attention has been paid to the relevance of customer perception… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(51 citation statements)
references
References 43 publications
0
51
0
Order By: Relevance
“…That is, the theory misses some important aspects of individuals' pro‐environmental decision making process beyond cognitive and normative dimensions (Gkargkavouzi et al, ; Han & Hyun, ; Onwezen et al, ; Zhang et al, ). Many recent studies in environmental consumer behavior, indeed, asserted attitudinal factors and environmental CSR as vital facets of such eco‐friendly decision‐related processes (Chen & Tung, ; Han, Yu, & Kim, ; Hwang & Ok, ; Martínez, Herrero, & Gómez‐López, ; Meng & Choi, ; Merli et al, ). These studies demonstrated the criticality of attitude and environmental CSR in reinforcing customers' pro‐environmental decision formation.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…That is, the theory misses some important aspects of individuals' pro‐environmental decision making process beyond cognitive and normative dimensions (Gkargkavouzi et al, ; Han & Hyun, ; Onwezen et al, ; Zhang et al, ). Many recent studies in environmental consumer behavior, indeed, asserted attitudinal factors and environmental CSR as vital facets of such eco‐friendly decision‐related processes (Chen & Tung, ; Han, Yu, & Kim, ; Hwang & Ok, ; Martínez, Herrero, & Gómez‐López, ; Meng & Choi, ; Merli et al, ). These studies demonstrated the criticality of attitude and environmental CSR in reinforcing customers' pro‐environmental decision formation.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…In both the practitioner and scholarly literatures, the adoption of certified EMSs has been associated with better environmental performance (e.g., Boiral, Guillaumie, Heras‐Saizarbitoria, & Tayo Tene, 2018; Martínez, Herrero, & Gómez‐López, 2019; Para‐González & Mascaraque‐Ramírez, 2019; Testa et al, 2014; Wagner, 2019), following the general trend in the scholarly literature that establishes a connection between the adoption of green practices and the improvement organization's performance (e.g., Franceschelli, Santoro, Giacosa, & Quaglia, 2019; Graafland & Smid, 2016). Nevertheless, the findings reported in the literature are not conclusive as this type of certification has also been associated with the improvement of corporate image and legitimacy among stakeholders, and greenwashing (e.g., Christmann & Taylor, 2006; Boiral, 2007; Heras‐Saizarbitoria, Dogui, & Boiral, 2013; Vílchez, 2017; Testa et al, 2018; Boiral, Heras‐Saizarbitoria, & Testa, 2017; Iatridis & Kesidou, 2018), and it remains controversial.…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, Oliver [40], Sarmiento and Ferrao [43] argue that clients begin to develop levels of loyalty when they are satisfied with the performance of the organization. Thus, Martínez [7] affirms that there is a relationship between satisfaction and loyalty in the hotel sector. In addition, he adds that customers will develop loyalty levels towards a hotel when they are satisfied with the service or the hotel's image.…”
Section: Loyalty As a Consequence Of The Green Imagementioning
confidence: 87%
“…Similarly, in recent years there has been a growing concern among consumers for environmental preservation and responsible consumption [3,4]. In this context, hotel consumers show a positive attitude towards green hotel practices, which motivates hotels to continue working to improve their environmental impact performance [5][6][7]. Hospitality companies and the industry, in general, should 2 of 17 be aware of current sustainability trends and strive to orient their innovation operations towards more sustainability-oriented companies, as this will not only create a good image and reduce cost but also safeguard the natural attraction for the frequent guests [8,9].…”
Section: Introductionmentioning
confidence: 99%